Optimization of Snackbar product formulation based on butterfly pea flower extract (Clitoria Ternatea L.) and canna tuber flour by d-optimal design expert mixture methods - Hariadi, Hari; Anggara, Cahya Edi Wahyu; Novianti, Fithria; Rahman, Nurhamidar; Rahman, Nurhaidar (International Journal of Innovative Research and Scientific Studies, 2025)
The purpose of this study was to determine the best formulation in making Snackbar Based on Butterfly Pea Flower Extract and Canna Tuber Flour using the Design Expert program, Mixture D-Optimal method. So as to obtain Snackbar Based on Butterfly Pea Flower Extract and Canna Tuber Flour with optimal chemical and organoleptic quality. Preliminary research verifies the formulation with organoleptic responses used to determine the upper and lower limits in the design expert program in the main research. The main research conducted was to determine the optimal formulation of Snackbar Based on butterfly Pea Flower Extract and Canna Tuber Flour by considering the changing variables, namely canna tuber flour, butterfly Pea flower extract, and palm ant sugar consisting of 5 stages including the formulation design stage, formulation stage, upper and lower limits, optimization stage, and verification stage using the Design Expert program D-Optimal method. The responses used include protein content, carbohydrate content, crude fiber content, fat content, ash content, total sugar content, water content, antioxidant activity, and organoleptic test. The selected formulation of Snackbar Based on butterfly pea Flower Extract and canna tuber Flour is 13.44% canna tuber flour, 13.54% ant palm sugar, 0.38% butterfly pea flower extract. The resulting desirability value is 0.686. Based on the results of verification in the laboratory, the moisture content was 6.66%, fat content was 17.22%, total sugar content was 13.90%, protein content was 10.27%, carbohydrate content was 62.79%, crude fiber content was 5.32%, ash content was 3.06%, color attribute score was 4.27 (rather like), aroma was 4.43 (rather like), taste was 4.33 (rather like), texture was 3.37 (rather dislike), and overall 3.53 (rather dislike).